Creating and evaluating a portal for urban educators - Sherry, L.; Conceicao, S.; Gibson, David (AACE, 2004)
The Teacher Education Network (TEN) PT3 Catalyst Grant, in conjunction with two of its partners, the Urban Network to Improve Teacher Education (UNITE) and the National Institute on Community Innovations (NICI), created an Urban Teacher Education Portal for its members that provided interactive and personalized access to a variety of digital resources and tools. The process used to create the portal and manage the digital resources is presented, using Richey and Nelson's (1996) Type I developmental research as the conceptual framework. A general analysis of the design, development, and evaluation process is followed by the results of three rounds of usability testing.